Axions in a Dispersed Medium: Light Scattering, Vavilov-Cherenkov Radiation (Global Journal of Science Frontier Research, 2023)
What happens to photons of laser radiation whose energy differs from the energy of the inter-level electronic transitions of atoms of the substance under study According to Bohr and Einstein the traditional scheme of interaction between radiation and matter includes the following processes 1 resonant absorption of radiation 2 spontaneous radiation 3 resonant stimulated radiation In the absence of resonance between the pumping frequency and the frequencies of electronic transitions in atoms alloying a dispersed medium the interaction of radiation and matter is carried out due to the annihilation of pairs of pump radiation photons the birth of axions and their subsequent decay into new photons whose energy differs from the energy of the pump photons If in atomic vapors in the resonant case one photon is required for the transition of an electron from the ground level S to the excited P then in the non-resonant case such a transition is possible due to the annihilation of a pair of photons